ANALISIS KRIMINOLOGIS TERHADAP TINDAK PIDANA PELECEHAN SEKSUAL DI KOTA MAKASSAR (Studi Kasus di Polrestabes Makassar): Case Study at Makassar Police Station - Nur Fadhilah Mappaselleng; Arya, Andi (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
This research moves from the anxiety over the rampant cases of sexual harassment in the city of Makassar, so the author is interested in further researching and analyzing the factors that cause criminal acts of sexual harassment in Makassar City, as well as seeing the efforts made by the Makassar Police in preventing and overcoming these criminal acts. This research uses empirical legal research method, which aims to observe and analyze the implementation of law in society. The results showed an increase in sexual harassment cases from year to year, namely in 2020, 2021, and 2022. The factors that cause sexual harassment involve internal and external factors. In an effort to prevent and overcome sexual harassment in the family, there are two approaches. First, through non-punitive countermeasures, involving pre-emptive and preventive measures that must be taken by individuals, communities, and the police. Second, through penal countermeasures, which include repressive measures taken by law enforcement officials such as the police, prosecutors, courts, and correctional institutions